A socio-cultural perspective to teacher adaptivity: the spreading of curricular innovations in Singapore schools. Issue 1 (2nd January 2016) - Lee, Shu-Shing; Hung, David
Abstract : This paper addresses how twenty-first century learning cultures can be enabled and spread in the Singapore school system by enacting curricular innovations and developing teachers' capacity for adaptivity. We appropriate understandings of adaptivity, including adaptive expertise, and contextualize it to the Singapore school system at the socio-cultural level of analysis. Our focus is on the socio-cultural enablers mediated by curricular innovations that influence teachers' learning of adaptivity. This socio-cultural perspective of teacher adaptivity is our contribution. The case study reveals that twenty-first century learning cultures and developing teachers' adaptivity are enabled by: (1) school leadership creating socio-technological provisions for teacher experimentation and innovation; (2) learning contexts that re-orientate pedagogy, curriculum, and assessment; (3) learning communities that build teacher capacity; and (4) historicity for developing adaptivity. While enablers can be appropriated from this case study to show how teacher learning occurred within the school, the spreading of teacher adaptivity to other schools cannot be naively replicated. We discuss these issues and postulate that diffusing teacher adaptivity requires leadership and socio-cultural dimensions to enact a process of teacher learning across schools for practices to be diffused.